Seed of an idea: Mann Ki Baat (Inner thoughts) programme and its perceived social influence on millets farming - GAUTAM, U S; MEERA, SHAIK N; SATYAVATHI, TARA; BHASKARAN, A; SANGAPPA; CHAPKE, R R; SINGH, RANJAY K (The Indian Journal of Agricultural Sciences, 2023)
The declining area and production of millets needed a national-level social influencer, and Mann Ki Baat hosted by the Hon’ble Prime Minister was timely. The present study tried to assess the perception of millet farmers, as to how social influencing event, such as Mann Ki Baat, has impacted millets farming context. The study was carried out in 68 districts belonging to 28 states and Union Territories with a participation of 1236 millet farmers, and professionals from 68 Krishi Vigyan Kendras (KVKs). The results indicated that the 88% of KVKs could undertake the follow-up activity on the Mann Ki Baat, and for attending a few episodes at KVK campuses, 60% of the farmers respondents travelled more than 15 KM. Among the millet farmers, 53% have listened to five Mann Ki Baat episodes, whereas 9% of the farmers have listened to more than 30 episodes (for general issues, going beyond agriculture-related episodes). This reveals that Mann Ki Baat, is no longer an urban-oriented program, but has directly reached out to the marginal millet farmers. Mass media and social media played a major role in publicizing the event among millet farmers and consumers, while KVKs provided knowledge support to millet farmers during and after the Mann Ki Baat episodes. About 20% of the farmers either formed or joined the Interest groups on millets after listening to the Mann Ki Baat. More than 45% of the farmers believed that they got at least one additional idea and or practice about millet farming due to this event. A considerable number of respondents either adopted or have been sensitized to what they were already doing, and further having millets in their diet after hearing the Mann Ki Baat episodes. The episodes had substantial influence on the perception of millet growers and consumers, which has strengthened further process of farmers’ adoption of improved varieties of millets and strengthened the environment on agri-entrepreneurship. The lessons learned from the study may help further to promote millet farming in accordance with changing agricultural scenarios locally and globally.